KARAKTERISTIK PENDERITA FIBROADENOMA MAMMAE (FAM) RAWAT INAP DI RS SANTA ELISABETH MEDAN TAHUN 2007-2011 - Helfiana Agustina Sidauruk; Rasmaliah .; Hiswani . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Fibroadenoma mammae is a benign tumors which are mainly found in young women. Prevalence of fibroadenoma occurred in more than 9% of the female population. There are 103 cases in Santa Elisabeth Hospital Medan during 2007-2011. To know the characteristics of fibroadenoma mammae patients who are hospitalized in Santa Elisabeth Hospital Medan descriptive study has been done by using case series design. The population and sample were 103 data patients (total sampling). Data was analyzed by using test of chi square and t- test. Proportion based on sosiodemography, highest age £ 35 years old 72,8%, Batak ethnic 77,7%, Protestant religion 55,4%, student 30,1%, not married 61,2%, lives in Medan 68%. Lies in the right breast 39,8%, the size of fibroadenoma £ 5 cm 82,7%, one fibrodenoma 55,3%, physical examination and radiological 54,4%, operation 98,1%, average length of stay 4,01 days, discharged under medical treatment 96,1%. There were significant differences between age and marital status (p=0.000), age with location of FAM (p=0,005), age with number of FAM (p=0.000) and the location of FAM with number of FAM (p = 0.000). There were no significant difference between marital status with the location of FAM (p=0.467), marital status with the number of FAM (p = 0.244), treatment time based on the average during medical treatment (p=0,599), and treatment time based on the average during the home state (p=0,452). Suggested at the hospital to complete the recording of the status of the card especially in relation to the fibroadenoma mammae such as education, body mass index, history of contraceptive, parity, family history, type of fibroadenoma and history of nursing. Keywords : Fibroadenoma mammae, characteristics of the patients